Photoproduction of neutral kaons on a liquid deuterium target in the threshold region - Tsukada, K.; Takahashi, T.; Watanabe, T.; Fujii, Y.; Futatsukawa, K.; Hashimoto, O.; Hirose, K.; Ito, K.; Kameoka, S.; Kanda, H.; Maeda, K.; Matsumura, A.; et al. (Physical review. C, Nuclear physics, 2008)
The photoproduction process of neutral kaons on a liquid deuterium target is investigated near the threshold region, E{sub {gamma}}=0.8-1.1 GeV. Ksup 0 events are reconstructed from positive and negative pions, and differential cross sections are derived. Experimental momentum spectra are compared with those calculated in the spectator model using a realistic deuteron wave function. Elementary amplitudes as given by recent isobar models and a simple phenomenological model are used to study the effect of the new data on the angular behavior of the elementary cross section. The data favor a backward-peaked angular distribution of the elementary n({gamma},Ksup 0){lambda} process, which provides additional constraints on current models of kaon photoproduction. The present study demonstrates that the n({gamma},Ksup 0){lambda} reaction can provide key information on the mechanism of the photoproduction of strangeness.